Physical compatibility of pentoxifylline and intravenous medications. - Senarathna, S.; Strunk, T.; Petrovski, M.; Batty, Kevin (2018)
OBJECTIVE: To investigate the physical and chemical compatibility of pentoxifylline (PTX) with a wide range of parenteral medications used in the neonatal intensive care setting. DESIGN: PTX and drug solutions were combined in glass phials and inspected visually for physical incompatibility. The chemical compatibility was evaluated on the basis of PTX concentrations. RESULTS: Precipitation, colour change or turbidity was not visible in any of the test mixtures, indicating no observed physical incompatibility or apparent risk of blockage in narrow-bore intravenous tubing. The PTX concentration was approximately 2.5% and 4.5% lower when combined with dopamine and amoxicillin, respectively. The PTX concentration ratios for all other combinations were in the range of 99%-102%. CONCLUSION: In simulated Y-site conditions, physical compatibility testing of PTX and 30 parenteral medications revealed no evidence of precipitation. Based on PTX concentration tests, it could be prudent to avoid mixing PTX with dopamine or amoxicillin.